Pendampingan Pencegahan Radikalisme Pada Pengampu Kebijakan di Desa ex-Transmigrasi - Hery Noer Aly; Dayun Riadi; Nurhadi Nurhadi; Rini Puspitasari (Manhaj: Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Bengkulu Province is an area that is not a crossing, and has a lot of forest, this condition makes Bengkulu a strategic place for the preparation of the terrorism agenda. This article aims to provide assistance and reorientation for policy makers in villages adjacent to forests to pay attention to preventing radicalism and terrorism. This assistance is in the early stages of research using a qualitative approach. The location of the research was carried out in an ex-Transmigration village. The results of this research and service conclude that there needs to be a strengthening of the role of religious leaders in explaining multicultural values to the community which is strengthened through the support of village policy makers, because without any systematic effort understanding radicalism can enter unnoticed by villagers who are still unfamiliar with interpreting information. verses that are prone to be misinterpreted